ST elevation occurring during stress testing - Diana Malouf; Marc Mugmon (Greater Baltimore Medical Center, 2016)
A case is presented of significant reversible ST elevation occurring during treadmill testing, and the coronary anatomy and subsequent course are described, indicating that ischemia is a potential cause of this electrocardiographic finding.